New Geranomyia crane flies (Diptera: Limoniidae) from Korea and Kunashir Island - Podenas, Sigitas (Zootaxa, 2016)
Geranomyia kunashir n. sp. from Kunashir Island (Far East of Russia), Geranomyia piagola n. sp. and Geranomyia semjina n. sp. from South Korea are described. Keys for all species of Korean Geranomyia are presented.